Recycling Surgical Mask as Acoustic Panel using Hand Lay-Up Methods - Fatmala, Rita Iva; Yulianti, Ian; Fianti, Fianti (Universitas Negeri Semarang, 2022)
The research was conducted to recycle surgical masks as acoustic panels using hand lay-up methods and to test their effectiveness in reducing noise using the tube method. The frequency used as a sound source is 495 Hz. Tests were carried out with variations in panel thickness, they are 1 cm, 2 cm, 3 cm, 4 cm, and 5 cm and three variations composite material, they are first layer, second layer and third layer of surgical mask. The panel test results show that the thicker acoustic panels are more effective in reducing noise based on the regression analysis that show the thicker panel from three variations composite material is 0.98, 0.99 and 0.96, respectively all of which are included in the very strong category. In addition, ANOVA analysis show that the thicker panels from all variation composite material respectively was 0.002, 0.001 and 0.009, they are showed the significant effect between the thickness of the panel and the effectiveness of the panel in reducing noise. Furthermore, based on the regression analysis from acoustic panels composite made of surgical masks from first layer, second layer and third layer were 8.24, 8.39 and 5.81, respectively the panel acoustic from second layer surgical masks are more effective to reduce the noise than other layer. Overall, it can be concluded that acoustic panels made of surgical masks are effective in reducing noise, as well as a solution to increasing surgical mask waste during the Covid-19 pandemic.